# ch03 - 3-1 3-2)2(2)23(22(22 =ssssYand the original ode was...

This preview shows pages 1–9. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 3-1 3-2 )2(2)23(22)(22+++=ssssYand the original ode was tydtdydtyd2sin222322=++with )()(==yyb)This is a unique result. c)The solution arguments can be found from )2()2)(1(222)(2++++=ssssYwhich in partial fraction form is 221)(22121++++++=sasasssYThus the solution will contain four functions of time e-t, e-2t, sin2t, cos2t3.3 a)Pulse width is obtained when x(t) = 0 Since x(t)= h at t: h -at= 0 or t= h/ab) x(t)= hS(t) atS(t)+ a(t -t)S(t-t) x(t)x(t)hslope = aslope = -aslope = -a3-3 c) 2221)(seshsaesashsXstst-+=+-=--d)Area under pulse = h t/2 3.4 a) f(t) = 5 S(t) 4 S(t-2) S(t- 6) =)(sF= ( 296s-2s-e-4e-51sb) x(t)=x1(t) + x2(t) + x3(t) + x4(t) = at a(t-tr)S(t -tr) -a(t-2tr)S(t-2tr) + a(t-3tr)S(t-3tr) following Eq. 3-101. Thus X(s) = [ ]stststrrreeesa3221---+--by utilizing the Real Translation Theorem Eq. 3-104. x(t)-a-ax2x3tr2tr3trx1x4aa3-4 3.5 T(t) = 20 S(t) + 3055tS(t) 3055(t-30) S(t-30) ( 29ssessessssT302302211305520130551305520)(---+=-+=3.6 a) 432)4)(3)(2()1()(321+++++=++++=sssssssssX1)4)(3()1(21=+++=-=sssss6)4)(2()1(32-=+++=-=sssss6)3)(2()1(43=+++=-=sssss463621)(+++-+=ssssX234and( )66tttx teee---=-+b) )2)(2)(3)(2(1)4)(3)(2(1)(2jsjsssssssssX-++++=++++=jsjjsjsssX2232)(333321+-+++++++=81)4)(3(1221-=+++=-=ssss132)4)(2(1322=+++=-=ssss20811384021)2)(3)(2(1233jjjjssssjjs+-=---=-+++=+-=3-5 tteetxtt2sin2081122cos2083213281)(32+ -++-=--tteett2sin104112cos10431328132+-+-=--c) 2212)1(1)1(4)(+++=++=sssssX(1) 3)4(12=+=-=ssIn Eq. 1, substitute any s-1 to determine 1. Arbitrarily using s=0, Eq. 1 gives 1or131141212=+=2)1(311)(+++=sssXand3ttx( t )ete--=+d) ( 29222214321111)(++=++=++=bsssssX13whereand22b= =tetetxtbt23sin32sin1)(2--==e) X(s) = sessss5.)3)(2(1-+++To invert, we first ignore the time delay term. Using the Heaviside expansion with the partial fraction expansion, 32)3)(2(1)(++++=+++=sCsBsAsssssXMultiply by sand let s0 3-6 A= 61)3)(2(1=Multiply by (s+2) and let s-2 B= 21)1)(2(1)32)(2(12=--=+--+-Multiply by (s+3) and let s-3 C= 32)1)(3(2)23)(3(13-=---=+--+-Then 33222161)(+-+++=ssssXtteetx32322161)(---+=Imposing shift theorem )5.(3)5.(2322161)5.()(-----+=-=tteetxtxfor t0.5 3.7 a) 221226)1()1(6)(sssssssY+==++=661222====sss26)(ssY=b)9)9()2(12)(23212+++=++=sssssssY3-7 Multiplying both sides by s(s2+9) ))(()9()2(123221ssss+++=+or 132219)(2412+++=+sssEquating coefficients of like powers of s, s2: 1+ 2= 0 s1: 3= 12 s: 91= 24 Solving simultaneously, 12,38,38321=-==91238138)(2++-+=ssssYc) 654)6)(5)(4()3)(2()(321+++++=+++++=sssssssssY1)6)(5()3)(2(41=++++=-=sssss6)6)(4()3)(2(52-=++++=-=sssss6)5)(4()3)(2(63=++++=-=sssss665641)(+++-+=ssssYd) [ ])2()22(1)2(1)1(1)(2222+++=+++=ssssssY= 2)22(2252243221+++++++++sssssss3-8 Multiplying both sides by )2()22(22+++sssgives 1 = 1s4+ 41s3+ 61s2+41s+ 2s3+42s2+62s+4...
View Full Document

{[ snackBarMessage ]}

### Page1 / 26

ch03 - 3-1 3-2)2(2)23(22(22 =ssssYand the original ode was...

This preview shows document pages 1 - 9. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online